Victims of cyberstalking in Serbia - Kovačević-Lepojević Marina; Lepojević Borko (Temida, 2009)
The aim of this paper is to present research findings on prevalence and characteristics of cyberstalking in Serbia. A web-based questionnaire was used to collect data from a group of respondents who were recruited by snowball sampling via e-mail. A total of 237 respondents completed the online questionnaire. The aim of the first part of this paper is to determine the notion of cyberstalking as well as, to review research about the prevalence and the nature of stalking. The main results are the following: 39,6 % of respondents reported stalking; every fourth stalking victim is a victims of cyberstalking; mostly, cyberstalking victims were female and perpetrators were male. Victims were stalked by: persistent sending of unwanted e-mails and telephone calls, spreading rumors, abusive and negative comments and threats, encouraged other users to harass, threaten or insult, manipulating with victim's personal data, sending malicious programs and files, etc. In Serbia, cyberstalking is not criminalized yet and there are no organizations to whom victims may appeal and ask for help. We are hoping that this research will raise the awareness on cyberstalking and serve as a base for further research and legal reforms regarding cyberstalking victimization in Serbia.